Knowledge seeking behaviours of pre interns and early career doctors in Sri Lanka: a cross sectional study. (December 2015) - Rodrigo, Chaturaka; Maduranga, Sachith; Withana, Milinda; Fernando, Deepika; Rajapakse, Senaka
Abstract Background Use of reference sources for medical knowledge has changed dramatically over the last two decades with the introduction of online sources of information. This study analyses the medical knowledge seeking behaviours of pre interns and early career doctors in Sri Lanka. Methods This cross sectional survey with a convenience sample was conducted at two sites targeting two groups; pre-intern doctors graduated from the Faculty of Medicine, University of Colombo and early career doctors following a postgraduate course at the National Hospital of Sri Lanka. The data collection tool was an online self-administered questionnaire (paper based questionnaires used on request) that probed the patterns of using reference sources for medical knowledge. Results and discussion The respondents comprised of 52 pre-interns and 34 early career doctors. A majority (98 %) had internet access. Early career doctors preferred online resources significantly more than the pre-interns. However, the utilization of online resources for evidence synthesis and planning research was unsatisfactory in both groups. A significant proportion (35 %) responded that they had never read a systematic review. Only one person in the entire sample had co-authored a review article. Conclusion The use of online resources by participants seems to be satisfactory with a majority shifting to reliable online resources as a reference point for medical knowledge. However, a closer look at the usage patterns reveal that online resources that can be used for more innovative tasks such as evidence synthesis are grossly under-utilized.